Women with IBD show higher psychophysiological burden in comparison to men with IBD - Schulz, Franziska; Foldenauer, Ann Christina; Weidmann, Lara; Thomann, Anne K.; Tal, Andrea Oliver; Plachta-Danielzik, Sandra; Krause, Thomas; Bokemeyer, Bernd; Zeuzem, Stefan; Kubesch, Alica; Blumenstein, Irina (Journal of Clinical Medicine, 2024)
Background: Inflammatory bowel disease (IBD) remains an incurable illness. Patients with IBD show gender-specific differences in various aspects of the disease. There is still uncertainty about the causality of the differences. Methods: The aim of this study was to determine the most relevant psychophysiological gender-specific differences in IBD. For this purpose, a questionnaire survey was conducted on disease activity and psychological concomitant diseases in patients with IBD (n = 300). Among the 218 patients with IBD who provided gender information, both genders were equally distributed. Results: Females with IBD are significantly more affected by IBD-related symptoms than men. Disease activity Scores Harvey-Bradshaw Index (HBI), Partial Mayo Score (pMAYO) showed no significant differences between the sexes in the subgroups with CD (HBI, m: 3 (IQR 1-6), w: 4 (IQR 2-8), p = 0.0677) and UC (pMAYO, m: 1 (IQR 0-4), w: 3 (IQR 0-5), p = 0.2118). IBD Questionnaire (IBDQ)shows significant differences in the gender-specific analysis. The mean value of the IBDQ total score of the female participants was 4.4 (SD 1.1) and that of men was 5.0 (SD 1.0) (p = 0.0002). Conclusions: There is a great need to investigate the causality of gender-specific differences in greater depth.
Gesehen am 22.04.2025